Measuring Maximum Head Circumference Within the Picture Archiving and Communication System: A Fully Automatic Approach - Yepes-Calderon, Fernando; Wihardja, Frisca; Sloan, Andrea; Kim, Janet; Nelson, Marvin D.; McComb, J. Gordon (Frontiers in Pediatrics, 2021)
This study describes an automatic technique to accurately determine the maximum head circumference (MHC) measurement from MRI studies within the Picture Archiving and Communications System and automatically adds this measurement to the final radiology report. Participants were selected through a retrospective chart review of patients diagnosed with hydrocephalus. Forty-nine pediatric patients born from 06/14/2000 to 12/13/2018 were included in the study. We created two 3D structures—one of them comprising of ten rings, the other encompassing four rings. The two structures mirror head circumference values along the age axis in the Nellhaus plot. The 3D printed structures were used to create MRI phantoms. Analytical obtainment of circumference values from the 3D objects and phantom images allowed for a fair estimation and correction of errors on the image-based-measuring instrument. Then, standard manual MHC measurements were performed and compared to values obtained from the patients’ MRI T1 images using the tuned instrument proposed in this document. The average difference between manual and automatic assessments in girls (n=20) was 1.7 ± 0.12 cm, while in boys (n = 29), it was 1.6 ± 0.09 cm. The difference between manual and MRI generated data (n = 49) was 1.6 ± 0.07 cm. This automatic application augments the more error-prone manual MHC measurement and adds a numerical value to the final radiology report as a standard application.